Response on Cheema U N, et al. (J Pak Med Assoc. 74: 1051-1054, June 2024) Film as an educational tool in medical pedagogy: A study on cinemeducation and its effectiveness - Usama Naveed Cheema; Sarmed Ibrahim; Nukhbat Ullah Awan; Haram Ashiq; Wagma Sarmed; Khalid Munir (Journal of the Pakistan Medical Association)
Madam, I am pleased to read the thoughtful commentaryon our article, "Film as an educational tool in medicalpedagogy: A study on cinemeducation and itseffectiveness," published in the Journal of the PakistanMedical Association (JPMA). The constructive feedbackhighlights important perspectives on cinemeducationand its role in modern medical pedagogy.The reader rightly emphasizes the diverse applications ofcinemeducation across medical disciplines, includingfamily medicine, psychiatry, palliative care, and ethics.This aligns with our study's core premise that films serveas a bridge between theoretical and practical learning byfostering engagement and critical thinking. As noted inthe commentary, cinemeducation offers immensepotential to enhance empathy, soft skills, and cognitivelearning—skills essential for healthcare professionals.